2004
DOI: 10.1063/1.1796271
|View full text |Cite
|
Sign up to set email alerts
|

Electric field and temperature effects on water in the narrow nonpolar pores of carbon nanotubes

Abstract: Water molecules in the narrow cylindrical pore of a (6,6) carbon nanotube form single-file chains with their dipoles collectively oriented either up or down along the tube axis. We study the interaction of such water chains with homogeneous electric fields for finite closed and infinite periodically replicated tubes. By evaluating the grand-canonical partition function term-by-term, we show that homogeneous electric fields favor the filling of previously empty nanotubes with water from the bulk phase. A two-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
268
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(295 citation statements)
references
References 37 publications
27
268
0
Order By: Relevance
“…[23][24][25] Several of these studies indicated that the magnitude of dewetting is sensitive to the nature of the solute-solvent attractive dispersion interactions. [19][20][21] A similar sensitivity was found in systems where the solutes carry charges or are exposed to an external electric field, e.g., electrostatic interactions have been shown to strongly affect the dewetting behavior of hydrophobic channels [26][27][28] and hydrophobic spherical nanosolutes. 29,30 Furthermore, two recent simulations of proteins supported the importance of solvent dewetting and its sensitivity in realistic biomolecular systems.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…[23][24][25] Several of these studies indicated that the magnitude of dewetting is sensitive to the nature of the solute-solvent attractive dispersion interactions. [19][20][21] A similar sensitivity was found in systems where the solutes carry charges or are exposed to an external electric field, e.g., electrostatic interactions have been shown to strongly affect the dewetting behavior of hydrophobic channels [26][27][28] and hydrophobic spherical nanosolutes. 29,30 Furthermore, two recent simulations of proteins supported the importance of solvent dewetting and its sensitivity in realistic biomolecular systems.…”
Section: Introductionmentioning
confidence: 76%
“…Importantly, this demonstrates that the present formalism captures the sensitivity of dewetting phenomena to specific solvent-solute interactions as reported in previous studies. 20,21,26,27,29,31,32 Note that the optimal shape function at ͉z͉Ӎ2 Å is closer to the solutes in VI compared to V due to the proximity of the charge to the interface. Clearly, the observed effects, particularly the transition from III to VI, cannot be described by existing solvation models which use the surface area ͑GB/SA or PB/SA͒ ͑Ref.…”
Section: Behavior Of the Shape Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carlo simulations 12,16 . An alternative setup, particularly suitable in Molecular Dynamics studies involves a simulation of both the confinement and bulk, field-free environment (reservoir) in equilibrium with each other 14,15 .…”
Section: Interactions Among Water Molecules Aligned By Applied Electrmentioning
confidence: 99%
“…For example, simulations of explicit water between platelike solutes revealed that hydrophobic attraction and dewetting phenomena are strongly sensitive to the nature of solute-solvent dispersion interactions [4,5]. Similarly, simulations of hydrophobic channels [6,7] and nanosolutes [8] have shown that electrostatic potentials strongly affect the dewetting behavior and potentials of mean force (pmf). A fully atomistic simulation of the folding of the two-domain protein BphC enzyme [9] further supported coupling by showing that the region between the two domains was completely dewetted when solvent-solute van der Waals (vdW) and electrostatic interactions were turned off, but accommodated 30% of the density of bulk water with the addition of vdW attractions, and 85%-90% with the addition of electrostatics, in accord with experimental results.…”
mentioning
confidence: 99%